Effects of Levonorgestrel Implants of One Rod and Two Rod on Lipid Profile, Follicle Stimulating Hormone (FSH), and Estradiol Levels in Acceptors : Efek Implan Levonorgestrel Satu Batang dan Dua Batang terhadap Profil Lipid, Kadar Follicle Stimulating Hormone (FSH), dan Estradiol pada Akseptor - Santa Maria; Heriyadi Manan; Theodorus Theodorus; Adnan Abadi (Indonesian Journal of Obstetrics and Gynecology, 2020)
Abstract Objective: To find out the comparison of the effect of one-rod and two-rod levonorgestrel implants on FSH, estradiol levels and increase in acceptor lipid profile after a 3-month evaluation in the Mother Hospital of Rika Amelia Palembang.Methods: This study was a phase III clinical trial, "Open" (Open Randomized Clinical Trial), carried out randomization by comparing two types of implant KB, namely levonorgestrel implants, one rod with two rods. This research was conducted at the RSAB Rika Amelia Palembang. Research time is 6 months from November 2018 - April 2019 or until the number of samples is fulfilled.Results: Based on the installation time, the average installation time using one rods LNG was 1.54 ± 0.11 minutes and the LNG for the two rods was 2.49 ± 0.26 minutes. Majority of patients having a normal blood pressure of 89.5% in one rod LNG and 68.4% in two rod LNG. The mean body mass index (BMI) of respondents using LNG implants one rod was 24.19 ± 3.93 kg / m2 and LNG for two rods was 25.09 ± 6.11 kg / m2. Based on the menstrual pattern, it was found that 84.2% of the subjects had regular menstrual patterns in the one-rod LNG group, while there were 63.2 % of subjects who have irregular menstrual patterns. From the statistical test, it was found that there were no differences in cholesterol levels (p = 0.919), HDL (p = 0.793), LDL (p = 0.851) and triglycerides (p = 0.679). There were no differences in FSH levels between respondents using one rod and two rod LNG implants (p = 0.849) and also on estradiol (p = 0.099)Conclusion: There is no difference between the use of one-rod and two-rodlevonorgestrel implants against FSH, Estradiol levels and increased lipid profile after 3 months of implant installation. The unpleasant effect in this study was the decline in HDL, but this was accompanied by a decrease in body weight, total cholesterol, LDL, HDL due to a decrease in all aspects.Keyword: estradiol, FSH, implant contraception, lenovorgestrel, lipid profile, one-rod, two-rod Abstrak Tujuan:Untuk mengetahui perbandingan efek implanlevonorgestrel satu-batang dan dua-batang pada FSH, kadar estradiol dan peningkatan profil lipid akseptor setelah evaluasi 3 bulan di Rumah Sakit Ibu Rika Amelia Palembang.Metode: Penelitian ini adalah uji klinis fase III, "Open" (Open Randomized Clinical Trial), yang dilakukan secara acak dengan membandingkan dua jenis KB implan, yaitu levonorgestrel implan, satu batang dengan dua batang. Penelitian ini dilakukan di RSAB Rika Amelia Palembang. Waktu penelitian adalah 6 bulan dari November 2018 - April 2019 atau hingga jumlah sampel terpenuhi.Hasil :Berdasarkan waktu pemasangan didapatkan rerata waktu pemasangan yang menggunakan LNG satubatangadalah 1,54±0,11 menitdanpada LNG dua batang adalah 2,49±0,26 menit. Mayoritas pasien memiliki tekanan darah yang normal 89.5% pada LNG satu batang dan 68.4% pada LNG dua batang. Rerata indeks massa tubuh (IMT) responden yang menggunakan implan LNG satu batang sebesar 24,19 ± 3,93 kg/m2 dan LNG dua batang sebesar 25,09 ± 6,11 kg/m2. Berdasarkan pola haid, didapatkan sebanyak 84,2% subjek yang memiliki pola haid teratur pada kelompok LNG satu batang, sedangkan terdapat sebanyak 63,2% subjek yang memiliki pola haid tidak teratur. Dari uji statistik didapatkan bahwa tidak terdapat perbedaan kadar kolesterol (p = 0,919), HDL (p = 0,793), LDL (p = 0,851) dan trigliserida (p = 0,679). Tidak terdapat perbedaan kadar FSH antara responden yang menggunakan implan LNG satu batang dan dua batang (p = 0,849) dan juga pada estradiol (p=0.099)Kesimpulan: Tidak terdapat perbedaan antara penggunaan implan levonorgestrel satu batang dan dua batang terhadap kadar FSH, Estradiol serta peningkatan profil lipid setelah 3 bulan pemasangan implan. Efek yang tidak menyenangkan dalam penelitian ini adalah terjaidnya penurunan HDL, namun hal ini disertai dengan penurunan berat badan, kolesterol total, LDL, HDL dikarenakan terjadi penurunan pada seluruh aspek.Kata Kunci: dua batang, estradiol, FSH, kontrasepsi implan, lenovorgestrel, profil lipid, satu batang.